Features of political participation of Russian youth in the context of digitalization - Alexander V. Anishchenko (Наука. Культура. Общество)
The article is devoted to identifying the specifics of the influence of the "digital" factor on the dynamics and transformation of political activity of modern Russian youth. The author pays special attention to the role of social networks and digital media on the political participation of the younger generation. Today, not only is the trend towards the emergence of diverse strategies for online political activity of Russian youth increasing, but significant changes are taking place in the differences in role models of political participation that differentiate passively engaged "viewers" and active activists. Those young Russians who actively use online resources in their socio-political activities are already quite effectively using digital technologies and ways to attract a new audience, social mobilization, finding supporters, coordinating joint actions, etc. It is noted that the key trend in recent years has been the "digitalization of political participation" of young people and the spread of the phenomenon of online political participation. The author concludes that despite the steady growth in the number of young users of social networks and consumers of digital media, the increasing role of these online resources as political factors should not be exaggerated in the process of political mobilization. The transformation of the socio-political context and the decrease in the general level of protest moods in society, the "calming down" of spontaneous mobilization in the "offline" certainly leads to a decrease in the mobilization value of social networks, and to a reduction in the number of protest-minded youth.